Study and restoration of the costume of the HuoLang (Peddler) in the Ming Dynasty of China - Zhu Chun; Gao Yuanyuan; Wang Jianping; Zeng Xianyi; Bruniaux Pascal; Liu Kaixuan (AUTEX Research Journal)
This study looks at two aspects of ancient Chinese genre painting to interpret the more realistic ancient shopping scenes in the painting of the peddler in spring scenery in the Ming Dynasty, namely, the Ming spring scene and the characters’ costume image features. Through the analysis of the detailed characteristics of the style, structure, pattern, and color of the figure costume in the painting of the peddler, a total of five sets of figure costume for an adult male and four children in the painting of the peddler in the spring scenery of the Ming Dynasty in China were digitally restored using the 3D virtual fitting technology, which clearly showed the characteristics of the figure costume of the peddler and children in the Ming Dynasty (1368–1644). The figure’s costume style in the painting of the salesman restored in the article is Beizi, closed crotch trousers, open crotch trousers, and abdominal circumference (a type of apron from the Song Dynasty. It is made to resemble a short apron and is wrapped around the abdomen). The study of the painting of peddler in the Ming dynasty in this work provides a reference for future study on ancient Chinese genre paintings of peddler and the restoration of the costumes of the figures in the painting.